2019
DOI: 10.1016/j.ifset.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Several melanosis-inhibiting formulas to enhance the quality of deepwater pink shrimp (Parapenaeus longirostris)

Abstract: The aim of this work was to assess the effect of several melanosis-inhibiting formulations on quality of deepwater pink shrimp (Parapenaeus longirostris) during storage. The formulations tested were as follows: one containing 4-hexylresorcinol (0.1%) in combination with organic acids (citric, ascorbic and acetic) and chelating agents (ethylenediaminetetraacetic acid [EDTA] and di-sodium di-hydrogen pyrophosphate [PPi]); a commercial formula based on sulphites (3%), and another formulation containing a mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…To confirm this, in the current work the TVB-N levels at day 8 were strongly positively correlated with the total viable count, psychrotrophic counts and pH ( p < 0.01; Table S2 ). Other authors reported similar or higher TVB-N values, suggesting that our shrimps were of good quality [ 36 , 38 , 41 ].…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…To confirm this, in the current work the TVB-N levels at day 8 were strongly positively correlated with the total viable count, psychrotrophic counts and pH ( p < 0.01; Table S2 ). Other authors reported similar or higher TVB-N values, suggesting that our shrimps were of good quality [ 36 , 38 , 41 ].…”
Section: Resultssupporting
confidence: 72%
“…Cadun et al [ 52 ] found that the addition of rosemary extract to a marination treatment with NaCl and organic acids reduced TVB-N and TBARS values, but it did not change the shrimp’s pH values during storage. Conversely, López-Caballero et al [ 41 ] found a slight increase in TVB-N using a formulation containing 4-hexylresorcinol, chelating agents and acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the European Union, the use of 4-HR as an antioxidant has been approved in fresh, frozen or deep-frozen crustacean meat, but maximum residue levels in the edible portion of the crustacean cannot exceed 2 mg/kg. Some studies support the effectiveness of 4-HR preventing melanosis in fresh crustaceans, including deep-water rose shrimp (López-Caballero, Martínez-Álvarez, Gómez-Guillén, & Montero, 2006b;López-Caballero, Martínez-Álvarez, Gómez-Guillén, & Montero, 2019). The use of polyphenols to avoid the appearance of black spots is another possibility that has received some attention among researchers (Nirmal, Benjakul, Ahmad, Arfat, & Panichayupakaranant, 2015;Sae-leaw & Benjakul, 2019).…”
mentioning
confidence: 99%
“…Color is among the most useful criteria in assessment of the quality level of aquatic food. The initial color of fishery products changed during cold storage affecting the quality (López-Caballero et al, 2019).…”
Section: Changes In Colormentioning
confidence: 99%